Case Report: An unusual case of hemoptysis - Li, Zhenhua; Yang, Zhen; Ni, Jixiang; Tang, Siyi; Xia, Dongping; Wang, Rujuan (Frontiers in Medicine, 2025)
We present a case of a 61-year-old woman with hemoptysis for 1 week. Two weeks prior, she underwent trigeminal microvascular decompression and repair of cerebrospinal fluid leakage under general anesthesia. Hemoptysis began 1 week after surgery, and examinations indicated intratracheal pseudoaneurysm. A definitive diagnostic evaluation confirmed that the formation of intratracheal pseudoaneurysm was related to tracheal intubation. This case highlights the fatal risk resulting from tracheal intubation. The patient was discovered after endovascular coiling. The utilization of endovascular approaches has gained popularity due to their minimally invasive nature, feasibility, and enhanced safety profile with reduced complications.